2020
DOI: 10.1007/s00296-020-04550-3
|View full text |Cite
|
Sign up to set email alerts
|

The importance of FDG PET/CT in the diagnostic process of the middle aortic syndrome in a 15-year-old boy patient with suspected systemic vasculitis and final diagnosis of Williams–Beuren syndrome

Abstract: The differential diagnosis in children with the systemic vasculopathy is still a challenge for clinicians. The progress in vascular imaging and the latest recommendations improve the diagnostic process, but only single reports describe the use of new imaging tests in children. The publication aims to demonstrate the important role of 18F-fluoro-2-deoxy-d-glucose (FDG) positron emission tomography combined with anatomical computed tomography angiography (PET/CTA) imaging in the case of a 15-year-old boy with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
0
1
Order By: Relevance
“…Violetta, et al previously reported a case of MAS due to WBS, which was firstly misdiagnosed as systemic vasculitis. 11) However, there are several differences between their case and the present case. For example, our patient was asymptomatic and had no typical facial dysmorphism and structural heart disease suggesting WBS.…”
Section: Discussioncontrasting
confidence: 52%
“…Violetta, et al previously reported a case of MAS due to WBS, which was firstly misdiagnosed as systemic vasculitis. 11) However, there are several differences between their case and the present case. For example, our patient was asymptomatic and had no typical facial dysmorphism and structural heart disease suggesting WBS.…”
Section: Discussioncontrasting
confidence: 52%